Digitalization as a Vector of Information Systems Development and Accounting System Modernization - Chyzhevska, Lyudmyla; Voloschuk, Lidiia; Shatskova, Liubov; Sokolenko, Liudmyla (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
Digitalization causes structural changes in the economic sectors and influences business activity and processes, leading to the companies’ increased productivity, competitive advantages and effective development creation and consolidation. This article is purposed to substantiate that the economy digitalization entails the need for companies' system and mechanisms modernization to ensure their competitiveness and to improve management systems. The research is conducted using methods of theoretical generalization, analysis, synthesis, comparison and grouping. This study resulted in defining both global and Ukrainian economies’ trends for digitalization with a description of its impact on the business activity and business processes, assessing the economy digitalization effects to the requirements for the company's information system that therefore serves to establishing directions for its modernization through the introduction of digital technologies, such as Electronic Data Interchange, Extensible Business Reporting Language, BigData, Internet of Things, Robotic Process Automation, Artificial intelligence, Real-time Adherence, cloud technologies, blockchain. The directions of companies' accounting digitalization implementation and development are as flows: changes in the accounting system in terms of its method elements; application of Assets, Liabilities and Capital new digital forms; advanced training in compliance with the requirements for the accounting personnel digital competencies.